2014
DOI: 10.1002/jemt.22386
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic observation of the sagittal structure ofDrosophilamature sperm

Abstract: Observation of sperm development and determination of their morphological characteristics are very important to the understanding of phylogenetic relationships and the study of sperm function during fertilization. Although ultrastructural studies of sperm development in the testes of the fruit fly Drosophila have been performed, there are few reports describing electron microscopic morphology of mature sperm, that is, those released from the testes to the seminal vesicles. Here, we present the first report of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Classic electron microscopy studies concluded that in many insects, the spermatid centrioles with 9 fold symmetry of microtubules disappear in mature sperm (Phillips, 1970 ). This is supported by observations from more recent electron microscopy studies of Drosophila's spermatozoa (Blachon et al, 2009 ; Yasuno and Yamamoto, 2014 ). In these observations, the microtubules of the centriole appear collapsed into a tight bundle at the proximal end.…”
Section: Centriole Inheritance During Reproductionsupporting
confidence: 67%
“…Classic electron microscopy studies concluded that in many insects, the spermatid centrioles with 9 fold symmetry of microtubules disappear in mature sperm (Phillips, 1970 ). This is supported by observations from more recent electron microscopy studies of Drosophila's spermatozoa (Blachon et al, 2009 ; Yasuno and Yamamoto, 2014 ). In these observations, the microtubules of the centriole appear collapsed into a tight bundle at the proximal end.…”
Section: Centriole Inheritance During Reproductionsupporting
confidence: 67%